University experience: The use of Whatsapp application as a pedagogical tool through the insertion of gamification and didactic choreography - Oliveira , Carlos Alexandre de; Martins , Charles Gomes (Seven Editora, 2023)
The pandemic was a difficult time of great social, economic, emotional and educational turmoil. School actors and families had to develop new skills in the face of Distance Education. With this we see that there was a greater commitment of parents to assume the responsibility of monitoring their children and providing guidance. Actions forgotten for a long time due to the fact that families transferred to the school the responsibility for educating their children. In view of these new demands, we seek to understand the use of whatsaap as a pedagogical tool for interaction with students through the use of didactic choreography and gamification. This experience report arose to meet the requirements of the discipline of University Teaching and Integration with the TDIC of PPGEdumatec / UFPE. During the discipline we tested tools and dialogued with theorists who moved us to research. DOI:https://doi.org/10.56238/ptoketheeducati-072